Advances and innovations in dialysis in the 21st century. Issue 1000 (27th March 2009) - Power, A; Duncan, N; Goodlad, C
Abstract : Patients with end stage renal failure (ESRD) require renal replacement therapy in the form of dialysis or renal transplantation. There is an increasing number of people receiving maintenance dialysis as patients with ESRD are increasing faster than the supply of transplantable organs. The mortality rate on dialysis is 4–6 times that of the general population and is substantially reduced by transplantation. For the past 8 years, dialysis research has focused on improving patient outcomes and quality of life on dialysis. This review examines recent advances in haemodialysis and peritoneal dialysis in a historical context and considers future research possibilities.